Radiographically normal knees with contralateral joint space narrowing display greater change in cartilage transverse relaxation time than those with normal contralateral knees: a model of early OA? – data from the Osteoarthritis Initiative (OAI) - Wirth, W.; Maschek, S.; Roemer, Frank; Sharma, L.; Duda, G. N.; Eckstein, F. (Osteoarthritis and Cartilage, 2019)
Objective: To develop a model of early osteoarthritis, by examining whether radiographically normal knees with contralateral joint space narrowing (JSN), but without contralateral trauma history, display greater longitudinal cartilage composition change (transverse relaxation time; T2) than subjects with bilaterally normal knees. Methods: 120 radiographically normal knees (Kellgren Lawrence grade [KLG] 0) from the Osteoarthritis Initiative were studied. 60 case knees displayed definite contralateral radiographic knee osteoarthritis (KLG ≥ 2) whereas 60 reference subjects were bilaterally KLG0, and were matched 1:1 to cases based on age, sex, and BMI. All had multi-echo spin-echo MRI acquired at year (Y) 1 and 4 follow-up, with cartilage T2 being determined in superficial and deep cartilage layers across 16 femorotibial subregions. T2 across all regions was considered the primary analytic focus. Results: Of 60 KLG0 case knees (30 female, age: 65.0 ± 8.8 y, BMI: 27.6 ± 4.4 kg/m2), 21/22/13/4 displayed contralateral JSN 0/1/2/3, respectively. The longitudinal increase in the deep layer cartilage T2 between Y1 and Y4 was significantly greater (P = 0.03; Cohen's D 0.50) in the 39 KLG0 case knees with contralateral JSN (1.2 ms; 95% confidence interval [CI] [0.4, 2.0]) than in matched KLG0 reference knees (0.1 ms; 95% CI [−0.5, 0.7]). No significant differences were identified in superficial T2 change. T2 at Y1 was significantly greater in case than in reference knees, particularly in the superficial layer of the medial compartment. Conclusions: Radiographically normal knees with contralateral, non-traumatic JSN represent an applicable model of early osteoarthritis, with deep layer cartilage composition (T2) changing more rapidly than in bilaterally normal knees. Clinicaltrials.gov identification: NCT00080171.
CRIS-Team Scopus Importer:2019-09-03
Keywords: Cartilage composition; Cartilage T2; Cartilage transverse relaxation time; Model of early osteoarthritis; MRI